Answer
a) (graph)
As t increases, y increases.
b) $x= -4y - 3$
$y=-\frac{1}{4}x-\frac{3}{4}$
![](https://gradesaver.s3.amazonaws.com/uploads/solution/69b408de-14fa-488c-9582-b0de5369c717/result_image/1504160412.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250215%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250215T144149Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=081784bae676d4aa5c4cba1fbcc10cef29476c0baf3d5b3ced1271fdf0875ce8)
Work Step by Step
a) t=-2
x=1- 2(-2)=5
y=(1/2)(-2)-1= -2
t=-1
x=1-2(-1)=3
y=(1/2)(-1)-1= -1.5
t=0
x=1-2(0)= 1 y=(1/2)(0)-1= -1
t=1
x=1-2(1)=-1
y=(1/2)(1)-1 = -0.5
t=2
x=1-2(2)= -3
y=(1/2)(2)-1 = 0
t=3
x=1-2(3)= -5
y=(1/2)(3)-1 = 0.5
t=4
x=1-2(4)= -7
y=(1/2)(4)-1 = 1
b) y= (1/2)t - 1
y+1=(1/2)t
2y+2=t
x=1-2t
x=1-2(2y+2)
x=1-4y-4
x=-4y-3